Agrotechniques for safed musli Chlorophytum borivilianum Sandaou and fernandes) in Kerala - Suma V K (Department of Agronomy, College of Agriculture, 2005)
A field experiment was conducted at the Instructional Farm attached to the College of Agriculture, Vellayani during the year 2004-2005, to study the adaptability and performance of safed musli under different sources of organic manures. Standardization of agro techniques such as planting weight of tuber and doses of nutrients were also undertaken. The experiment was laid out in factorial randomised block design with three replications. The treatments consisted of five sources of organic manures - M1 – FYM @ 30 t ha-1 (farmers’ practice), M2 – vermicompost, M3 – 50 per cent FYM + 50 per cent vermicompost, M4 – 50 per cent FYM + 50 per cent groundnut cake, M5 – 50 per cent FYM + 50 per cent neem cake and M6 (control), viz., FYM @ 10 t ha-1 as basal + NPK @ 100 : 80 : 80 kg ha-1 and two different planting weight of tubers such as 10 g unit-1 (P1) and 15 g unit-1 (P2). Organic manure and planting weight of tuber had significant influence on most of the growth and yield attributing characters of safed musli. The fresh and dry tuber yield of safed musli as well as saponin content were also influenced by treatments. Results of the study revealed that application of organic manure as 50 per cent FYM + 50 per cent groundnut cake significantly improved the growth characters like plant spread, number of suckers hill-1 and number of leaves plant-1 and physiological parameters like LAI, LAD and TBR. Similar trend was also observed for yield and yield attributing characters like length, diameter and number of tubers. Among the quality parameters, fresh and dry weight of tuber after peeling and saponin content were highest in the treatment where 50 per cent FYM + 50 per cent groundnut cake was applied as organic source. The N, P and K uptake were maximum in 50 per cent FYM + 50 per cent groundnut cake applied plots. The available N and K content in soil were the highest in 50 per cent FYM + 50 per cent neem cake treated plots where as P availability was maximum in plots that received nutrients as 50 per cent FYM + 50 per cent groundnut cake. Planting weight of tuber also significantly influenced the various growth and yield attributing characters. The growth characters like plant spread, number of suckers hill-1 and number of leaves plant-1 and physiological parameters like LAI, LAD and TBR were the highest in treatments where 15 g unit–1 weight of tuber was used as planting material. The yield, yield attributing characters and quality parameters were also the maximum in the same treatment. The uptake and availability of nutrients were also the maximum in the treatment where higher planting weight of tuber was used (15 g unit–1). Economic analysis revealed that planting safed musli @ 15 g unit-1 weight of tuber and applying nutrients as 50 per cent FYM + 50 per cent groundnut cake could fetch maximum net return whereas for getting the highest BCR, it is wise to use 10 g unit-1 weight of planting material along with 50 per cent FYM + 50 per cent groundnut cake.